Buffalo hump and cervical lipoma - Contreras-Grande, Jheferson (2023)
We report two cases of cervical masses in a 32 and 36-year-old women. The cervical CT scan showed in one an abnormal accumulation of subcutaneous cellular tissue giving the phenotype of “buffalo hump”; in the other patient an ovoid lesion of fatty density with a fine capsule, in keeping with lipoma. The buffalo jump is associated with an excessive production of estrogens, either endogenous or exogenous steroid excess (Cushing’s disease, adrenal or pituitary tumors), use of certain antiretrovirals in AIDS patients (protease inhibitors), obesity and Madelung’s disease. While lipomas are benign tumors of the fat tissue that may be located in the cervico-dorsal area and may mimic a jump. Differentiating these two entities is key, as the management differs significantly. The correction of the underlying condition in patients with buffalo jump is indicated, while surgical removal is the mainstay therapy for lipomas.